“YEA” or “NAY” in Psychology Science: An Analysis of the Postmodern Nature of Performing Psychology (Asian Education Studies, 2017)
Since becoming an independent subject, psychology has portrayed itself as a strict science on the way to thedevelopment of natural science. Because of breaking away from the social cultural and historical background ofhuman life, scientific psychology is being questioned. In the doubt, non scientific psychology which is closer tosocial life and can adapt to the human need emerges as the times require. Performance psychology developingfrom social therapy insists on a new cultural-performatory approach to understanding human life, makingpsychology research return to life and helping people to restart their development. Non-epistemology,non-diagnosis and non-adaptability are the essential embodiment of performing psychology from the naturalscience to the post-modern humanities.